English language assessment in Indonesian senior high schools: Perceived challenges and prospective solutions - Muhammad Nur Akbar Rasyid; Alfian Alfian; Jumharia Djamereng; Nurwahida Nurwahida (Universitas Islam Negeri Palangka Raya, Indonesia, 2024)
Numerous scholarly investigations have been conducted on English language assessment practices. Nevertheless, there is a lack of knowledge regarding the challenges and potential solutions related to implementing effective language assessment practices, particularly within Indonesian senior high schools. This study aims to investigate the perceived constraints and aspired prospective solutions associated with language assessment practices in Indonesian EFL classrooms. The data for this qualitative case study were collected by conducting in-depth interviews with fifteen EFL teachers from different senior high schools across South Sulawesi, Indonesia. Based on the thematic analysis of the data, this study revealed the perceived challenges to implementing English language assessment practices in three general categories: national policy-related issues, institution-related issues, and student-teacher-related issues. This study also revealed the need for leadership support to foster school culture support for innovative language assessment practices as the main aspired solution to implementing language assessment practices. These findings help improve understanding of the numerous factors that must be considered when putting English language assessment into practice, theoretically and practically.